Silenced by violence: mental health impact of Colombia’s armed conflict on women - Valentina Belalcazar-Vivas (BJPsych International)
Colombia’s armed conflict has deeply impacted women’s mental health, particularly in rural and marginalised areas, where violence has become normalised. Despite legal recognition of mental health as a right, access to care remains limited due to geographic, cultural, systemic and security barriers. Mental health programmes lack continuity and funding, while professional training, availability and research in trauma-informed care are still insufficient. Institutional mistrust and ongoing threats further silence women’s suffering. This paper describes the current state of mental health services for women affected by armed conflict in Colombia and reflects on the persistent challenges.